1999
DOI: 10.2337/diabetes.48.7.1487
|View full text |Cite
|
Sign up to set email alerts
|

Leptin restores euglycemia and normalizes glucose turnover in insulin-deficient diabetes in the rat.

Abstract: Leptin has been shown to improve insulin sensitivity and glucose metabolism in normoinsulinemic healthy or obese rodents. It has not been determined whether leptin may act independently of insulin in regulating energy metabolism in vivo. The present study was designed to examine the effects of leptin treatment alone on glucose metabolism in insulin-deficient streptozotocin (STZ)-induced diabetic rats. Four groups of STZ-induced diabetic rats were studied: 1) rats treated with recombinant methionine murine lept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
156
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 0 publications
14
156
1
8
Order By: Relevance
“…The direct effects of leptin on glucose metabolism and insulin signaling have not yet been fully elucidated. However, in vivo studies have shown that leptin improves insulin sensitivity (Ebihara et al, 2001;Lin et al, 2002;Ogawa et al, 1999;Yamauchi et al, 2001) and normalize glucose metabolism in rodents (Chinookoswong et al, 1999;Masuzaki et al, 1999). Transgenic expression of neuron-specific leptin receptor in receptor-deficient mice leads to amelioration of diabetes (de Luca et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The direct effects of leptin on glucose metabolism and insulin signaling have not yet been fully elucidated. However, in vivo studies have shown that leptin improves insulin sensitivity (Ebihara et al, 2001;Lin et al, 2002;Ogawa et al, 1999;Yamauchi et al, 2001) and normalize glucose metabolism in rodents (Chinookoswong et al, 1999;Masuzaki et al, 1999). Transgenic expression of neuron-specific leptin receptor in receptor-deficient mice leads to amelioration of diabetes (de Luca et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs études chez des rongeurs insulinodéficients ont suggéré que l'administration de leptine pourrait traiter le diabète ou améliorer l'effet de l'insuline [14][15][16][17]. La première étude, publiée en 1999 [15], a pris pour modèle des rats traités par la streptozotocine, et a montré que l'infusion sous-cutanée de leptine, en l'absence d'insulinothéra-pie, pouvait normaliser les glycémies.…”
Section: Amélioration Par La Leptine Des Effets De L'insulineunclassified
“…La première étude, publiée en 1999 [15], a pris pour modèle des rats traités par la streptozotocine, et a montré que l'infusion sous-cutanée de leptine, en l'absence d'insulinothéra-pie, pouvait normaliser les glycémies. Ces résultats sont en faveur d'un rôle insulino-indépendant de la leptine sur le métabolisme glucidique, permettant à la fois de diminuer la production hépatique de glucose et d'augmenter son utilisation périphérique en l'absence d'insuline.…”
Section: Amélioration Par La Leptine Des Effets De L'insulineunclassified
“…2,8,10,15,23,33,34 In this context, recent attention has been devoted to the disclosure that dynamic physiological fluctuations in circulating titers of leptin, a hormone produced primarily by white adipose tissue under the direction of insulin, have a critical role in conferring glucose homeostasis indirectly through the central nervous system. 10,16,[35][36][37][38][39][40][41][42] The goals of this review are to collate major contributions emanating from research conducted with the aid of gene transfer technology in unraveling the neural etiology of this chronic disease of hyperglycemia, which is correctable by leptin gene therapy confined selectively to the hypothalamus, and that this neurotherapy can be gainfully employed to forestall the pathogenesis of diabetes and varied attendant comorbidities.…”
Section: Introductionmentioning
confidence: 99%